Acute Fibrinous and Organizing Pneumonia Associated With Allogenic Hematopoietic Stem Cell Transplant Successfully Treated With Corticosteroids - Lam-Phuong Nguyen DO; Stella Ahdoot MD; Narin Sriratanaviriyakul MD; Yanhong Zhang MD; Nicholas Stollenwerk MD; Michael Schivo MD; Richart Harper MD (Journal of Investigative Medicine High Impact Case Reports, 2016)
Acute fibrinous and organizing pneumonia (AFOP) is an extremely rare, relatively new, and distinct histological pattern of acute lung injury characterized predominately by the presence of intra-alveolar fibrin and associated organizing pneumonia. AFOP may be idiopathic or associated with a wide spectrum of clinical conditions. It has a variable clinical presentation from mild respiratory symptoms to that similar to the acute respiratory distress syndrome. Currently there is no consensus on treatment, and corticosteroids previously were of unclear benefit. To date, there are less than 40 cases of AFOP reported in the literature and only one has been linked to hematopoietic stem cell transplantation. Here we report the first case series of 2 patients who developed AFOP following allogenic stem cell transplant that were successfully treated with high-dose corticosteroids.